Combination of Analytic Hierarchy Process (AHP) Method and Profile Matching Method with Matrix Decomposition in Determining Olympiad Candidates - ismail Hanif Batubara; Indah Purnama sari (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
One of the government's programs in improving the quality of human resources is by organizing the selection of candidates for the Olympics which aims to improve general knowledge. To be able to take part in the selection of prospective participants for the Olympics, the participants have general knowledge, achievements, behavior and experience in following closely at the high school level.There are several problems in the selection of students at the school level, including teachers or principals in selecting students only based on the value of the lessons obtained, even though the Olympics are held at the district, provincial and national levels, other factors are needed including knowledge, achievement and experience in participating in the competition. previous olympics so the results were not optimal.Therefore, it is necessary to design a decision support system using the AHP (Analytical Hierarchy Process) and Profile Matching methods which are expected to assist decision makers in obtaining information for selecting the right students to participate in the Olympics.After testing and analysis involving manual calculations, it can be seen that the results obtained from system calculations are the same as manual calculations. So that this system can be used to help schools or teachers to select students in participating in the Olympics at the High School (SMA) level.